2021
DOI: 10.31557/apjcp.2021.22.3.661
|View full text |Cite
|
Sign up to set email alerts
|

Opium Usage and Risk of Head and Neck Cancer: A Systematic Review and Meta-Analysis

Abstract: Estimates from 2019 suggest that there are approximately 54 million opium users worldwide, 80% of whom live in Asia. Ease of access, and traditional beliefs about opium are the two factors responsible for high rate of consumption (Hosseini et al., 2010) Opium use or abuse leads to several acute health hazards and some reports also states association between use long term effects of opium use and risk of cancer. Link between opium and oral, bladder, lung, head and neck and gastric cancers have been found in pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…We also conducted an appraisal of the most important aspects of study quality, and documented a lack of cumulative exposure information, which might be further explored in future studies of opium consumption and cancer risk. Although other meta-analyses have been recently published on opium consumption and cancer risk [10][11][12][13][14], our systematic review is the most up to date, and has carefully considered a range of methodological sources of bias in findings, according to domains of study quality assessment defined by the IARC Monographs volume 126 Working Group.…”
Section: Random Effects Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We also conducted an appraisal of the most important aspects of study quality, and documented a lack of cumulative exposure information, which might be further explored in future studies of opium consumption and cancer risk. Although other meta-analyses have been recently published on opium consumption and cancer risk [10][11][12][13][14], our systematic review is the most up to date, and has carefully considered a range of methodological sources of bias in findings, according to domains of study quality assessment defined by the IARC Monographs volume 126 Working Group.…”
Section: Random Effects Modelmentioning
confidence: 99%
“…Here, we aimed to supplement the recent qualitative IARC cancer hazard evaluation by conducting an extended systematic review and a quantitative meta-analytic assessment of the role of opium consumption and risk for selected cancers, including cancers of the urinary bladder, larynx, lung, oesophagus, stomach, and pancreas [9]. This analysis therefore represents the most comprehensive systematic review and meta-analysis to date [10][11][12][13][14]. We specifically considered in detail exposure assessment quality, and the impact of various potential methodological sources of bias and confounding on meta-analytic findings according to a registered protocol.…”
Section: Introductionmentioning
confidence: 99%
“…In Iran, a case-control study found a significant relationship between opium addiction and OSCC, with an OR of 4 CI [1.2-13.6] [83], and a recent meta-analysis found a four-fold rise in the risk of head and neck cancer among opium users compared to non-users [84].…”
Section: Other Addictionsmentioning
confidence: 99%
“…The correlation between the risk of tumour formation and opium consumption has been reported by many studies [13,14]. The positive and negative effect of opium is still a controversial matter for the last few years [15,16].…”
Section: Introductionmentioning
confidence: 99%